Chemical Composition Acorus Calamus L. - Arabova Nodira Ziyodovna (Peerian Journals Publishing, 2023)
In this article, the information on the chemical composition of the prospective medicinal plant Acorus calamus in Uzbekistan is presented. There are 2 species belonging to the genus Acorus L., and the species Acorus calamus L. is found in Uzbekistan. The plant contains bitter acorin glycoside, 25% starch, tar, alkaloids and flavoring substances, tannins, up to 150% vitamin C and vitamin B. The composition of the essential oil includes pinene, camphene, camphor, merneol, eugelol, azarone, guaene, selinene, acorone, roazilene and other substances.
Keywords: Acorus calamus; medicinal features; chemical composition